Silica powder

JP2025031499APending Publication Date: 2025-03-07DENKA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024064103
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、樹脂に配合したときの低誘電正接および充填性に優れたシリカ粉末が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031499000001
    Figure 2025031499000001
Patent Text Reader

Abstract

To provide a silica powder excellent in a low dielectric loss tangent and filling properties when blended into a resin.SOLUTION: Silica powder according to the present invention has: a dielectric loss tangent of at most 2.0×10-3 at 40 GHz in a resin sheet sample, as measured by a resonance method; a specific surface area from 0.2 m2 / g to 5.0 m2 / g inclusive, as measured by a BET 1-point method using nitrogen gas adsorption; a frequency of at least 5.5% for a maximum peak in a particle diameter frequency distribution as measured by a wet laser diffraction scattering method; a frequency of at most 6.0% for particles having a particle diameter of at least 20.7 μm in the particle diameter frequency distribution; and Dm / S reaching at least 1.50, where Dm (μm) refers to a value of a mode diameter in the particle diameter frequency distribution, and S (m2 / g) refers to a value of the specific surface area.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silica powder. [Background technology]

[0002] In recent years, with the increase in the amount of information and communication in the field of communication, the use of high frequency bands in electronic devices and communication devices is spreading. High frequency bands have characteristics such as wide bandwidth, straightness, and transparency. 9 The GHz band, which is above 100 GHz, is widely used.

[0003] The use of high frequencies has led to problems such as increased transmission loss of circuit signals. Transmission loss can be broadly divided into conductor loss caused by the skin effect of wiring, and dielectric loss caused by the characteristics of the dielectric material of the insulators that make up electrical and electronic components such as circuit boards. Dielectric loss is proportional to the first power of frequency, the half power of the dielectric constant of the insulator, and the first power of the dielectric dissipation factor, so materials used in high frequency devices are required to have both low dielectric constant and dielectric dissipation factor.

[0004] Silica (SiO2) has a low dielectric constant (3.7) and a quality factor index Qf (the inverse of the dielectric tangent multiplied by the measurement frequency) of approximately 120,000, making it a promising filler material with low dielectric constant and dielectric tangent. However, the surfaces of silica particles contain a large amount of adsorbed water and polar functional groups such as silanol groups, and in particular there is a problem in that the dielectric loss tangent is worse than the properties of the sintered substrate.

[0005] In response to this, Non-Patent Document 1 discusses a method of surface treatment with a silane coupling agent as a method for reducing adsorbed water and polar functional groups on the surface of filler particles. However, the dielectric tangent is hardly reduced at 1 to 10 MHz, and the effect is insufficient, and the effect in the GHz band is not clearly stated. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] IEEE Transactions on Dielectrics and Electrical Insulation Vol. 17, No. 6(2010) Summary of the Invention [Problem to be solved by the invention]

[0007] However, as a result of investigations by the present inventors, it was found that the silica powder described in Non-Patent Document 1 above still has room for improvement in terms of low dielectric tangent and filling property when blended with a resin. [Means for solving the problem]

[0008] As a result of further investigation, the present inventors have found that by appropriately adjusting the particle size characteristics of "frequency of maximum peak," "frequency of particles having a particle size of 20.7 μm or more" in the particle size frequency distribution, and "mode diameter / specific surface area" in a silica powder having a predetermined "specific surface area," it is possible to improve the fillability of the silica powder into a resin while lowering the dielectric tangent when the silica powder is blended with the resin, and have thus completed the present invention.

[0009] According to one aspect of the present invention, there is provided a silica powder comprising: 1. The dielectric loss tangent of a resin sheet sample at 40 GHz measured according to the following procedure is 2.0×10 -3 A silica powder having the following structure: The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.0m 2 / g or less, The frequency of the maximum peak in the particle size frequency distribution measured by a wet laser diffraction scattering method is 5.5% or more. The frequency of particles having a particle size of 20.7 μm or more in the particle size frequency distribution is 6.0% or less; and The value of the most frequent diameter in the particle size frequency distribution is Dm (μm), and the value of the specific surface area is S (m 2 / g), Dm / S is 1.50 or more. Silica powder. (procedure) The silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resin sheet sample is molded using the obtained mixed powder.The dielectric loss tangent at 40 GHz is measured using the obtained resin sheet sample by a resonance method. 2. The silica powder according to 1., The silica powder has a mode diameter of 1.0 μm or more and 15.0 μm or less. 3. The silica powder according to 1. or 2., A silica powder, in which the frequency of particles having a particle size of 2.01 μm or less in the particle size frequency distribution is 2.0% or less. 4. A silica powder according to any one of 1. to 3., The particle size at the point where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 90% is defined as D 90 Then, D 90 The silica powder has a particle size of 3.0 μm or more and 25.0 μm or less. 5. A silica powder according to any one of 1. to 4., The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 10%, 50%, and 100% are defined as D 10 , D 50 , D 100 Then, (D 100 -D 10 ) / D 50 The silica powder, wherein the molecular weight is 5.0 or less. 6. The silica powder according to any one of 1. to 5., 1. or 2. The silica powder according to claim 1, Silica powder that generates less than 700 ppm of moisture by the time it reaches 200°C, as measured by the Karl Fischer method. 7. The silica powder according to any one of 1. to 6., A silica powder having an average sphericity of 0.85 or more. 8. The silica powder according to any one of 1. to 7., Silica powder having an amorphous rate of 95.0% or more. 9. The silica powder according to any one of 1. to 8., Silica powder containing uranium and thorium elements at levels of 20 ppb or less. Effect of the Invention

[0010] According to the present invention, there is provided a silica powder which has a low dielectric tangent and excellent filling properties when blended with a resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The silica powder of this embodiment will be outlined below.

[0012] The silica powder of this embodiment is The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.0m 2 / g or less, The frequency of the maximum peak in the particle size frequency distribution measured by a wet laser diffraction scattering method is 5.5% or more. The frequency of particles with a particle size of 20.7 μm or more in the particle size frequency distribution is 6.0% or less, and The most frequent diameter in the particle size frequency distribution is Dm (μm), and the specific surface area is S (m 2 / g), Dm / S is 1.50 or more.

[0013] According to the findings of the present inventors, it has been found that by appropriately adjusting particle size characteristics such as the "frequency of the maximum peak" in the particle size frequency distribution, the "frequency of particles with a particle size of 20.7 μm or more," and the "modal diameter / specific surface area" of a silica powder having a predetermined "specific surface area," it is possible to reduce the dielectric tangent when the powder is blended with a resin and improve the fillability into the resin. Although the detailed mechanism is unclear, it is presumed that by appropriately controlling the particle size characteristics as described above, the filling state of the silica powder in the resin becomes more appropriate, making it possible to reduce the dielectric tangent of the resin sheet. In addition, the resin composition containing the silica powder having the appropriate particle size characteristics as described above has high resin permeability into narrow gaps, so that the silica powder can be highly filled. This makes it possible to reduce the dielectric loss tangent of a thin molded article of the resin composition.

[0014] The silica powder of this embodiment has a dielectric loss tangent of 2.0×10 at 40 GHz of the resin sheet measured by the following procedure. -3 It satisfies the following: The upper limit of the dielectric tangent at 40 GHz is 2.0×10 -3 Less than or equal to 1.9×10 -3 Less than or equal to 1.5×10 -3 Less than 0.5×10, more preferably -3 The following is the result. The lower limit of the dielectric loss tangent at 40 GHz is not particularly limited, but is, for example, 1.0×10 -6 It may be more than that.

[0015] (Measuring procedure for dielectric tangent) Silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resulting mixed powder is used to mold a resin sheet sample. The dielectric loss tangent at 40 GHz is measured using the resulting resin sheet sample by the resonance method.

[0016] The silica powder of the present embodiment can be suitably used as a filler to be mixed into resin materials such as resins or resin compositions. The resin materials can be used for various purposes, and can be used, for example, as high-frequency resin materials.

[0017] The composition of the silica powder of this embodiment will be described in detail below.

[0018] <Silica powder> The silica powder may be any powder containing silica (SiO2) as a main component. The term "main component" means that the silica powder contains, for example, 50% or more, preferably 80% or more, and more preferably 90% or more, of silica (SiO2) in terms of mass, based on the total amount of the silica powder. The silica powder preferably has a high purity, but the presence of impurities that are inevitably mixed in from the raw materials or during the production process is acceptable.

[0019] The silica powder may be either or both of amorphous and crystalline. The amorphous rate of the silica powder is, for example, 95.0% or more, preferably 97.0% or more, and more preferably 99.0% or more.

[0020] The amorphous ratio of the silica powder is measured by X-ray diffraction analysis using a powder X-ray diffractometer (for example, Model MiniFlex manufactured by RIGAKU Corporation) in the 2θ range of 26° to 27.5° with CuKα radiation, and is measured from the intensity ratio of specific diffraction peaks. In the case of siliceous powders, crystalline silica has a main peak at 26.7°, but amorphous silica has no peak. When amorphous silica and crystalline silica are mixed, the height of the peak at 26.7° depends on the proportion of crystalline silica. Then, the crystalline silica mixing ratio (X-ray diffraction intensity of sample / X-ray diffraction intensity of crystalline silica) can be calculated from the ratio of the X-ray intensity of the sample to the X-ray intensity of the crystalline silica standard sample, and the amorphous ratio (%) can be calculated from the formula, amorphous ratio (%) = (1 - crystalline silica mixing ratio) x 100.

[0021] The shape of the silica powder may be any of spherical, crushed, needle-like, flake-like, etc., but the spherical shape is preferred.

[0022] The average circularity of the silica powder is, for example, 0.85 or more, preferably 0.90 or more, and more preferably 0.95 or more, which can suppress an increase in viscosity and a decrease in flowability when the silica powder is mixed with a resin.

[0023] The average sphericity of the silica powder is measured as follows. Particle images taken with a stereomicroscope (for example, Nikon Model "SMZ-10"), a scanning electron microscope, or the like, are input into an image analyzer (for example, Nippon Avionics Co., Ltd.). The projected area (A) and perimeter (PM) of the particle are measured from the photograph. If the area of ​​a perfect circle corresponding to the perimeter (PM) is (B), the circularity of the particle can be expressed as A / B. If we assume a perfect circle with the same perimeter as the perimeter (PM) of the sample particle, PM=2πr, B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity of each particle is given by: Sphericity = A / B = A × 4π / (PM) 2 It can be calculated as follows: The circularity of 200 randomly selected particles thus obtained was determined, and the average value was taken as the average sphericity.

[0024] The upper limit of the specific surface area of ​​silica powder is 5.0 m 2 / g or less, preferably 4.5m 2 / g or less, more preferably 4.0m 2 / g or less. This makes it possible to reduce the dielectric tangent when blended with a resin. On the other hand, the lower limit of the BET specific surface area is 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 This makes it possible to suppress a decrease in fluidity when blended with a resin.

[0025] The specific surface area of ​​the silica powder can be measured by the BET one-point method using nitrogen gas adsorption. Specifically, a specific surface area measuring device (manufactured by Anton Paar, device name: NOVA 800 BET) is used, nitrogen gas is transported as the adsorption gas by a vacuum pump, and 0.1 to 5.0 g of the sample is dried and degassed at 300°C for 30 minutes before measurement.

[0026] The upper limit of the frequency of the maximum peak in the particle size frequency distribution of the silica powder is not particularly limited, but is, for example, 20% or less, preferably 18% or less, and more preferably 15% or less. On the other hand, the lower limit of the frequency of the maximum peak is 5.5% or more, preferably 5.6% or more, and more preferably 5.7% or more. The particle size frequency distribution that satisfies the lower limit of the frequency of the maximum peak has a relatively sharp profile. This can improve the filling property of the resin material containing the silica powder.

[0027] In addition, the number of peaks showing a frequency maximum within the range of 1.0 μm or more and 15.0 μm or less in the particle size frequency distribution of the silica powder may be one or more. When a silica powder has multiple peaks, the peak with the highest frequency is defined as the "maximum peak."

[0028] The upper limit of the most frequent diameter in the particle diameter frequency distribution of the silica powder is, for example, 15.0 μm or less, preferably 14.0 μm or less, and more preferably 13.0 μm or less, which can further improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the mode diameter is, for example, 1.0 μm or more, preferably 2.0 μm or more, and more preferably 3.0 μm or more, which can suppress an increase in viscosity of the resin material containing the silica powder.

[0029] The most frequent diameter in the particle size frequency distribution of the silica powder is Dm (μm), and the specific surface area of ​​the silica powder is S (m 2 / g), and the value of the most frequent diameter / the specific surface area is defined as Dm / S. The upper limit of Dm / S in the silica powder is not particularly limited, but is, for example, not more than 50, preferably not more than 40, and more preferably not more than 30. This can further improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the Dm / S is 1.50 or more, preferably 1.60 or more, and more preferably 1.70 or more, which can improve the filling property of the resin material containing the silica powder.

[0030] The upper limit of the frequency of particles having a particle diameter of 20.7 μm or more in the particle diameter frequency distribution of the silica powder is 6.0% or less, preferably 3.0% or less, and more preferably 1.0% or less, which can improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the frequency of particles having a particle size of 20.7 μm or more is not particularly limited, but may be 0% or more.

[0031] The upper limit of the frequency of particles having a particle diameter of 2.01 μm or less in the particle diameter frequency distribution of the silica powder is, for example, 2.0% or less, preferably 1.0% or less, and more preferably 0.8% or less, which can suppress an increase in viscosity of the resin material containing the silica powder. On the other hand, the lower limit of the frequency of particles having a particle size of 2.01 μm or less is not particularly limited, but may be 0% or more.

[0032] The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution of silica particles is 10%, 50%, 90%, and 100% are D 10 , D 50 , D 90 , D 100 Let us assume that.

[0033] D 90 The upper limit of the particle size is, for example, 25.0 μm or less, preferably 21.0 μm or less, and more preferably 18.0 μm or less. This can further improve the filling property of the resin material containing the silica powder. On the other hand, D 90 The lower limit of the silica powder is, for example, 3.0 μm or more, preferably 4.0 μm or more, and more preferably 5.0 μm or more. This makes it possible to suppress an increase in viscosity of the resin material containing the silica powder.

[0034] (D 100 -D 10 ) / D 50 is, for example, 5.0 or less, preferably 4.5 or less, and more preferably 4.0 or less, whereby an increase in viscosity of the resin material containing the silica powder can be suppressed. On the other hand, (D 100 -D 10 ) / D50 The lower limit is, for example, 0.3 or more, preferably 0.7 or more, and more preferably 1.0 or more.

[0035] The particle size frequency distribution and volume frequency particle size distribution of silica powder are values ​​based on particle size measurement by a wet laser diffraction light scattering method, and can be measured using, for example, a particle size distribution measuring device, LS13 320 manufactured by Coulter. When measuring, water is used as a solvent, and as a pretreatment, a dispersion treatment can be performed by applying 500W output using a homogenizer for 120 seconds or more. In addition, the PIDS (Polarization Intensity Differential Scattering) concentration is adjusted to 45 to 55%. The refractive index of water is 1.33, and the refractive index of the powder is determined by considering the refractive index of the powder material. For example, the refractive index of amorphous silica is measured at 1.50.

[0036] In the silica powder, the upper limit of the amount of moisture (physically adsorbed water) generated before the temperature reaches 200° C. as measured by the Karl Fischer method is, for example, 700 ppm or less, preferably 600 ppm or less, and more preferably 500 ppm or less, which can further reduce the dielectric tangent when blended with a resin. On the other hand, the lower limit of the physically adsorbed water is not particularly limited, but may be 0 ppm or more, or 1 ppm or more.

[0037] The water content in the silica powder is measured by the Karl Fischer method. Specifically, a trace moisture measuring device (Mitsubishi Chemical Corporation, Model CA-05) was used, the powder was placed in a quartz tube in a moisture vaporization mechanism, and dehydrated argon gas was supplied as a carrier gas while heating from room temperature to 900°C with an electric heater, and the water vapor evaporated from the powder surface was guided to the moisture measurement mechanism to measure the moisture content. The moisture generated before the heating temperature of the electric heater reached 200°C was considered to be physically adsorbed water.

[0038] The upper limit of the content of uranium and thorium in the silica powder is, for example, 20 ppb or less, preferably 10 ppb or less, and more preferably 1.0 ppb or less, which can suppress the occurrence of defects in devices such as memories. On the other hand, the lower limits of the contents of the uranium and thorium elements are not particularly limited, but may be, for example, 0.1 ppb or more.

[0039] The content of uranium and thorium elements in the silica powder is measured using an inductively coupled plasma mass spectrometer (ICP-MS).

[0040] In this embodiment, for example, by appropriately selecting the raw material components of the silica powder and the manufacturing method of the silica powder, it is possible to control the above-mentioned dielectric loss tangent, specific surface area, various values ​​obtained from the particle size frequency distribution, and various values ​​obtained from the volume frequency particle size distribution. Among these, for example, using silica powder manufactured by a dry method, removing powder on the coarse powder side and removing powder on the fine powder side in combination, etc., are listed as elements for making the above-mentioned dielectric loss tangent, specific surface area, various values ​​obtained from the particle size frequency distribution, and various values ​​obtained from the volume frequency particle size distribution within the desired numerical range.

[0041] <Method of manufacturing silica powder> As an example of the manufacturing method of the present embodiment, raw material silica powder manufactured by a dry method is subjected to a coarse powder classification process, and then to a fine powder classification process, thereby obtaining silica powder. In addition, the classification process can be carried out by mixing or classifying appropriate amounts of silica powders having different particle size configurations. Industrially, classification using a classifier such as a sieve or a precision air classifier is desirable, and the classification operation is preferably a dry method. By dry classifying raw silica powder produced by a dry method, it is possible to suppress aggregation of the silica powder and improve handleability, etc., compared to the case where raw silica powder produced by a wet method and / or wet classification is used. The obtained silica powder is desirably stored in a moisture-proof bag.

[0042] The classified silica powder may be subjected to a heat treatment as one of the post-treatments. The heat treatment is performed in a hot air or electric furnace at a temperature of 500 to 1100°C for a predetermined time (e.g., about 1 to 52 hours) such that heating temperature (°C) × heating time (h) is 1000 to 26400 (°C·h), preferably for a predetermined time (e.g., about 2 to 35 hours) such that heating temperature (°C) × heating time (h) is 1800 to 17600 (°C·h). If the heating temperature is 500 to 1100°C, the specific surface area and average particle size do not change before and after heating, so it is desirable to carry out the classification process before heating and then adjust the specific surface area and average particle size to the desired values ​​before carrying out the heat treatment. After the heat treatment, the silica powder is naturally cooled in the electric furnace, and then collected at 110°C to 300°C. It is further cooled to 25°C in an environment with a humidity of 40% RH or less, and stored at 15 to 25°C. It may also be collected and stored in a moisture-proof aluminum bag.

[0043] The classified silica powder may be subjected to a surface treatment as one of post-treatments. The surface treatment can be performed with a surface treatment agent to further reduce the surface polar groups and the dielectric loss tangent. The surface treatment agent is preferably one that does not leave polar functional groups after the surface treatment, such as hexamethyldisilazane. After the surface treatment, it is desirable to collect the material again in a moisture-proof aluminum bag.

[0044] The method for storing silica powder is to store it in a container with a moisture permeability of 0.1 (g / m2) under condition B of JIS Z 0208-1976 (temperature 40°C, relative humidity 90%). 2 It is preferable to store the product in a moisture-proof bag for up to 24 hours, such as a moisture-proof aluminum bag or a PET / AL / PE laminate bag.

[0045] Next, the resin composition of the present embodiment will be described. A resin composition containing the silica powder of this embodiment can be suitably used as a resin material. The resin composition contains, in addition to the silica powder of this embodiment, a resin and known resin additives.

[0046] In the resin composition, the silica powder may be used alone or may be mixed with other fillers. The resin composition may contain 10 to 99% by mass of the silica powder, or 10 to 99% by mass of a mixed inorganic powder containing the silica powder and other fillers. The content of the other fillers in the mixed inorganic powder may be, for example, 1 to 20% by mass or 3 to 15% by mass relative to 100% by mass of the silica powder. In this specification, the symbol "to" indicates that both the upper and lower limits are included, unless otherwise specified.

[0047] Examples of other fillers include silica other than the silica powder of this embodiment, alumina, titania, silicon nitride, aluminum nitride, silicon carbide, talc, calcium carbonate, and the like. The other fillers have an average particle size of about 5 to 100 μm, and there are no particular restrictions on the particle size composition and shape.

[0048] Examples of the resin include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide such as polyimide, polyamideimide, polyetherimide, polyester such as polybutylene terephthalate, polyethylene terephthalate, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. These may be used alone or in combination of two or more.

[0049] The resin composition can be produced, for example, by blending raw material components in a predetermined ratio using a blender or a Henschel mixer, kneading the mixture using a heated roll, a kneader, a single-screw or twin-screw extruder, or the like, cooling the mixture, and then pulverizing it.

[0050] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES

[0051] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples. <Preparation of Silica Powder> [Examples 1 to 10] The silica powder was prepared according to the following procedure. The raw material used was commercially available silica powder A produced by a dry method. Silica powder A used as the raw material had one mode diameter peak in the range of 1.0 to 15.0 μm.

[0052] (Coarse powder classification) First, the raw silica powder was subjected to coarse particle classification using sieves with various opening sizes in order to remove large particles. The particle size frequency distribution showed the frequency of particles with a particle size of 20.7 μm or more as shown in Table 1.

[0053] (Fine powder classification) Next, the silica powder after the coarse classification was subjected to fine classification using a precision air classifier to cut off the fine powder side. The frequency of particles with a particle size of 2.01 μm or less in the particle size frequency distribution was obtained as shown in Table 1.

[0054] (Post-treatment 1: Heat treatment) The silica powders of Examples 3, 8 and 10 were subjected to fine powder classification and then to a heat treatment. In the heat treatment, the silica powder was filled into an alumina crucible and heat-treated in air at 1000°C in an electric furnace for 4 hours. After the heat treatment, it was cooled to 200°C in the furnace and then cooled to room temperature in a desiccator (23°C, 10% RH), and the heat-treated silica powder was collected.

[0055] (Post-processing 2: Surface treatment) The silica powder of Example 9 was subjected to fine powder classification and then to a surface treatment. In the surface treatment, 1 part by mass of methacrylsilane (manufactured by Shin-Etsu Silicones) was added to 100 parts by mass of silica powder, mixed in a vibration mixer (manufactured by Resodyn), and then dried at 200°C for 4 hours to recover the surface-treated silica powder.

[0056] [Comparative Example 1] Commercially available silica powder B produced by a dry process was used. Silica powder B had no mode diameter peak in the range of 1.0 to 15.0 μm, and had one mode diameter peak in the range exceeding 15.0 μm.

[0057] [Comparative Example 2] The raw material used was commercially available silica powder C produced by a dry method. Silica powder C had one mode diameter peak in the range of 1.0 to 15.0 μm. Silica powder C was used and only the above-mentioned (coarse powder classification) was carried out to obtain silica powder.

[0058] [Comparative Example 3] Silica powder C was used and only the above-mentioned (coarse powder classification) and (post-treatment 1: heat treatment) were carried out to obtain silica powder.

[0059] [Comparative Example 4] The raw material used was commercially available silica powder D produced by a dry method. Silica powder D had one mode diameter peak in the range of 1.0 to 15.0 μm. Silica powder D was used and only the above-mentioned (coarse powder classification) was carried out to obtain silica powder.

[0060] [Comparative Example 5] Silica powder D was used and only the above-mentioned (coarse powder classification) and (post-treatment 1: heat treatment) were carried out to obtain silica powder.

[0061] The silica powder obtained in each of the Examples and Comparative Examples was stored in an aluminum bag until immediately before various evaluations.

[0062] [Table 1]

[0063] The obtained silica powder was evaluated for the following items.

[0064] <Dielectric loss tangent measured by the resonance method> The silica powder was mixed with polyethylene powder (Sumitomo Seika Chemicals, Flowthen UF-20S) to a loading of 40 volume % using a vibration mixer (Resodyn) under conditions of an acceleration of 60 g and a processing time of 2 minutes. The obtained mixed powder was weighed out to a specified volume (so that the thickness was about 0.3 mm), placed in a metal frame with a diameter of 3 cm, and molded in a heat press machine (Imoto Manufacturing Co., Ltd. "IMC-1674-A type") under molding conditions of 140°C, 10 MPa, and 15 minutes to mold a resin sheet sample of 1.5 cm square and 0.3 mm thick. Note that the shape and size of the resin sheet sample do not affect the evaluation results as long as it can be mounted on the measuring device. Using the obtained resin sheet sample, a 40 GHz cavity resonator (manufactured by Samtec) was connected to a vector network analyzer (85107, manufactured by Keysight Technologies), and the 10 mm diameter hole in the resonator was set to be blocked, and the resonant frequency (f0) and unloaded Q value (Qu) were measured. The sample was rotated for each measurement, and the measurement was repeated five times in the same manner. The average of the obtained f0 and Qu was taken as the measured value. The dielectric constant was calculated from f0, and the dielectric loss tangent (tan δc) was calculated from Qu using analysis software (SAMTECH software). The measurement temperature was 20°C, and the humidity was 60% RH. The obtained tan δc was defined as the dielectric tangent of the resin sheet sample.

[0065] <Specific surface area> The specific surface area of ​​the silica powder was measured by the BET one-point method using nitrogen gas adsorption. Specifically, a specific surface area measuring device (manufactured by Anton Paar, device name: NOVA 800 BET) was used, nitrogen gas was transported by a vacuum pump, and 0.1 to 5.0 g of sample was dried and degassed at 300° C. for 30 minutes before measurement.

[0066] <Particle size> The particle size frequency distribution and volume frequency particle size distribution of the silica powder were determined by a wet laser diffraction scattering method using a particle size distribution measuring device (LS13 320, manufactured by Coulter). Water was used as the solvent, and as a pretreatment, the powder was dispersed using a homogenizer at an output of 500 W for 120 seconds or more and measured. In addition, the PIDS (Polarization Intensity Differential Scattering) concentration was adjusted to 45 to 55% and measured. The refractive index of water was 1.33, and the refractive index of the powder was determined by considering the refractive index of the powder material. For example, the refractive index of amorphous silica was measured at 1.50. Based on the obtained particle size frequency distribution, the "mode diameter," "frequency of the maximum peak," "frequency of particle sizes less than 0.5 μm," "frequency of particle sizes 0.5 μm to less than 13 μm," and "frequency of particle sizes 13 μm or more" were calculated. Based on the obtained volume frequency particle size distribution, the particle size (D X ) was calculated.

[0067] <Average sphericity> The average sphericity of silica powder was measured by importing particle images taken with a stereomicroscope (e.g., Nikon Model "SMZ-10") or scanning electron microscope into an image analyzer (e.g., Nippon Avionics Co., Ltd.) as follows. That is, the projected area (A) and perimeter (PM) of the particle were measured from the photograph. If the area of ​​a perfect circle corresponding to the perimeter (PM) is (B), the circularity of the particle can be expressed as A / B. Therefore, assuming a perfect circle with the same perimeter as the perimeter (PM) of the sample particle, PM=2πr and B=πr 2 Therefore, B = π × (PM / 2π) 2The sphericity of each particle is given by: Sphericity = A / B = A × 4π / (PM) 2 The circularity of 200 randomly selected particles thus obtained was determined, and the average value was taken as the average sphericity.

[0068] <Moisture content> The water content in the silica powder was measured by the Karl Fischer method. Specifically, a trace moisture measuring device (Model CA-05, manufactured by Mitsubishi Chemical Corporation) was used. The powder was placed in a quartz tube in a moisture vaporization mechanism, and heated from room temperature to 900°C using an electric heater while dehydrated argon gas was supplied as a carrier gas. The water vapor evaporated from the powder surface was introduced into the moisture measurement mechanism to measure the moisture content. The moisture generated before the heating temperature of the electric heater reached 200°C was considered to be physically adsorbed water, the moisture generated between 200°C and 550°C was considered to be water derived from hydrogen-bonded OH groups, and the moisture generated between 550°C and 900°C was considered to be water due to dehydration condensation of isolated OH groups.

[0069] <Amorphous ratio> The amorphous ratio of the silica powder was measured from the intensity ratio of specific diffraction peaks by X-ray diffraction analysis using a powder X-ray diffractometer (manufactured by RIGAKU Corporation, product name "Model MiniFlex") in the 2θ range of 26° to 27.5° with CuKα radiation. Specifically, the crystalline silica mixing ratio (X-ray diffraction intensity of sample / X-ray diffraction intensity of crystalline silica) was calculated from the ratio of the X-ray intensity of the sample (obtained silica powder) to the X-ray intensity of the crystalline silica standard sample, and the amorphous ratio (%) was calculated from the formula: amorphous ratio (%) = (1 - crystalline silica mixing ratio) × 100.

[0070] <Uranium and thorium content> The uranium and thorium content (ppb) of the silica powder was measured using an inductively coupled plasma mass spectrometer (ICP-MS).

[0071] <Viscosity> 35% by mass of the obtained silica powder and 65% by mass of a liquid epoxy resin (bisphenol F type resin, JER807, manufactured by Mitsubishi Chemical Corporation) were mixed to obtain a resin sample. The viscosity (Pa s) of the obtained resin samples was measured at 25°C and a shear rate of 1 [1 / s] using a rheometer equipped with a conical cone (3 degrees) (Anton Paar, Model Modular Compact Rheometer MCR 102). The results are shown in Table 1.

[0072] <Evaluation of filling ability in narrow gaps> 60 g of the obtained silica powder, 40 g of liquid epoxy resin (Mitsubishi Chemical Corporation, bisphenol F type resin, JER807), and 0.06 g of a silane coupling agent (Shin-Etsu Chemical Co., Ltd., phenylaminotrimethoxysilane) were mixed to obtain a liquid filling sample. The two cleaned glass plates were placed with their surfaces facing each other and fixed to a jig so that the gap between them was 50 μm in thickness. The jig was placed on a horizontal table so that the two glass plates were horizontal. The glass plate was then placed on a hot plate, heated, and maintained at about 95°C. 0.2 mL of the above filling sample was dropped into the gap of the glass plate (thickness: 50 μm, width: 30 mm). The dropped filling sample gradually penetrated from the gap of the glass plate toward the inside. The state of penetration 5 minutes after the start of dropping was photographed. From the photographs taken, the percentage (%) of the filling sample that was filled in an area of ​​3 mm widthwise × 3 mm inward near the center of the gap opening was quantified, and the resin penetration rate was calculated. When the resin penetration rate was 40% or more, the filling property was judged to be excellent, when it was 10% or more and less than 40%, the filling property was judged to be poor, and when it was less than 10%, the filling property was judged to be very poor.

[0073] The silica powders of Examples 1 to 10 were able to reduce the dielectric tangent when blended with a resin, and showed superior results in narrow gap filling properties when blended with a resin compared to Comparative Examples 1 to 5.

Claims

1. The dielectric loss tangent of the resin sheet sample at 40 GHz measured according to the following procedure is 2.0 x 10 -3 A silica powder having the following structure: The frequency of the maximum peak in the particle size frequency distribution measured by a wet laser diffraction scattering method is 5.5% or more, The frequency of particles having a particle size of 20.7 μm or more in the particle size frequency distribution is 6.0% or less; The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.0m 2 / g or less, and The value of the most frequent diameter in the particle size frequency distribution is Dm (μm), and the value of the specific surface area is S (m 2 / g), Dm / S is 1.50 or more, Silica powder. (procedure) The silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resin sheet sample is molded using the obtained mixed powder. The dielectric loss tangent at 40 GHz is measured using the obtained resin sheet sample by a resonance method.

2. 2. The silica powder according to claim 1 , The silica powder has a mode diameter of 1.0 μm or more and 15.0 μm or less.

3. 3. The silica powder according to claim 1 or 2, A silica powder, in which the frequency of particles having a particle diameter of 2.01 μm or less in the particle diameter frequency distribution is 2.0% or less.

4. 3. The silica powder according to claim 1 or 2, The particle diameter at the point where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 90% is defined as D 90 When this is done, D 90 The silica powder has a particle size of 3.0 μm or more and 25.0 μm or less.

5. 3. The silica powder according to claim 1 or 2, The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 10%, 50%, and 100% are defined as D 10 , D 50 , D 100 When this is done, (D 100 -D 10 ) / D 50 The silica powder has a molecular weight of 5.0 or less.

6. 3. The silica powder according to claim 1 or 2, A silica powder in which the amount of moisture generated by the temperature reaching 200°C is 700 ppm or less as measured by the Karl Fischer method.

7. 3. The silica powder according to claim 1 or 2, A silica powder having an average sphericity of 0.85 or more.

8. 3. The silica powder according to claim 1 or 2, Silica powder having an amorphous rate of 95.0% or more.

9. 3. The silica powder according to claim 1 or 2, A silica powder having an elemental uranium and elemental thorium content of 20 ppb or less.